Vascular endothelial growth factor and biphasic calcium phosphate in the endosseous healing of femoral defects: An experimental rat study - Elçin Bedeloğlu; Selim Ersanlı; Volkan Arısan (Elsevier, 2017)
Background/purpose: The presence of adequate bone volume is a critical factor in rehabilitative dentistry. Despite the use of many promising alloplasts, success in stimulating bone formation has been limited, mostly due to poor local biological response. Growth factors have been introduced to stimulate angiogenesis and new bone formation. This histologic and histomorphometric study aimed to evaluate the effect of vascular endothelial growth factor (VEGF) and a biphasic alloplastic graft material (BA) on the healing of endosseous defects in rats. Materials and methods: Twenty male Wistar rats were used. Two critical-sized bone defects were created in both the right and left femurs of each rat. Each defect was randomly assigned to be treated with VEGF, BA, or VEGF + BA, or to be left empty as a control. Half of the animals were sacrificed after 1 week, and the remaining half were sacrificed after 2 weeks. Inflammation, necrosis, and new bone areas were evaluated by means of histologic and histomorphometric analyses. Results: Compared to the control group, defects treated with VEGF alone or in combination with BA showed higher rates of bone formation (33.10-46.60%) on Day 7. Additionally, VEGF significantly reduced inflammation and necrosis (P < 0.001). However, the differences were no longer discernable on Day 14. Conclusion: VEGF makes a significant contribution to angiogenesis and osteogenesis in the early stages of bone defect healing, and its combination with an osteoconductive grafting material (BA) may further enhance new bone formation.